The use of “electronic cloud” technology to improve the functioning of the recovery system of armored weapons and equipment - Kopashynskii, Serhiy; Serpukhov, Oleksandr; Makogon, Helen (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject matter of the article is the process of the system of recovery of armored weapons and equipment functioning in the performance of tasks for the purpose in modern conditions. The goal of the study is to create a decision support system for the recovery of armored weapons and equipment under the interactive analysis of temporal and spatial indicators of warfare based on the use of “electronic cloud " technology. The tasks to be solved are: to formulate tasks effectiveness will increase in the decision support system; to develope structural and functional-logical scheme of the system, the list of external, calculation and control modules; to determinate the volume and format of input and output information for each structural unit and information buses of the system; to define the format of protocols for information exchange, the content of “survey ” cards. General scientific and special methods of scientific knowledge are used. On the basis of a systematic analysis of the existing of armored weapons and military equipment recovery system, the main conditions and factors affect its functioning in modern armed conflicts were determined. The following results are obtained. The synthesis of the structural and logical scheme of the decision support system “virtual headquarters” in the form of software with modular architecture was carried out. Conclusions. Today, not only the process of positioning forces and means of technical support and their rational placement relative to military units, but also rapid response to changes in the technical situation is complicated. Improving the quality of the of weapons and military equipment recovery system is possible by creating a decision support system "Virtual headquarters". The main idea of creating the system is the processing of incoming and outgoing information in interactive mode, operational and optimal management of information flows and visualization of the solution for the recovery of weapons and military equipment. The proposed modular system architecture provides a list of external, design and management modules; the scope and format ofinput and output information for every business unit and information system buses. The information space, where the system resources will be located, is proposed to be built using the "electronic cloud" technology.

Предметом вивчення в статті є процес функціонування системи відновлення бронетанкового озброєння і техніки при виконанні завдань за призначенням в сучасних умовах. Метою дослідження є створення системи підтримки прийняття рішення з відновлення бронетанкового озброєння і техніки в умовах інтерактивного аналізу часово-просторових показників ведення бойових дій на основі використання технології “електронної хмари”. Задачі: Формулювання завдань, ефективність вирішення яких підвищиться у системі підтримки прийняття рішення; розробка структурної та функціонально-логічної схеми системи, переліку зовнішніх, розрахункових та управляючих модулів; визначення обсягу та формату вхідної та вихідної інформації для кожної структурної одиниці та інформаційних шин системи; формування протоколів обміну інформацією, змісту “опитувальних” карток. Методологічною основою дослідження стали загальнонаукові та спеціальні методи наукового пізнання. Hа основі системного аналізу існуючої системи відновлення бронетанкового озброєння і техніки були визначені основні умови і чинники, які впливають на її функціонування всучасних збройних конфліктах. Отримані такі результати. Було здійснено синтез структурно-логічної схеми системи підтримки прийняття рішення “віртуальний штаб” у вигляді програмного забезпечення з модульною архітектурою. Висновки. Сьогодні ускладнюється не тільки процес позиціонування сил і засобів технічного забезпечення та їх раціонального розміщення відносно військових підрозділів, а і оперативного реагування на зміну технічної обстановки. Підвищення якості функціонування системи відновлення озброєння та військової техніки можливо за рахунок створення системи підтримки прийняття рішення “Віртуальний штаб”. Провідною ідеєю створення системи є обробка вхідної та вихідної інформації в інтерактивному режимі, оперативне і оптимальне управління інформаційними потоками та візуалізація рішення по відновленню озброєння та військової техніки. Запропонована модульна архітектура системи, визначений перелік зовнішніх, розрахункових та управляючих модулів; обсяг і формат вхідної та вихідної інформації для кожної структурної одиниці таінформаційних шин системи. Інформаційний простір, де будуть знаходитися ресурси системи, пропонується побудувати за технологією “електронної хмари”.
Застосування технології “електронної хмари” для вдосконалення функціонування системи відновлення бронетанкового озброєння і техніки
Keywords: decision support system; virtual headquarters; система підтримки прийняття рішення; віртуальний штаб